(3aj CUhd EYQGH GdbQBf (B/s - (3GdaQfhGfj, gGfjs ((3GdOeGe (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3ecJHI GdeJfHj ,s, 2018)
(3gPG GdcJGH gh eMGhdI dGSJNdGU GdCUhd hGdVhGHW GdJj MceJ Yed GdYdeGA aj EYQGH GdbQBf HgOa HdhQI gPg GdVhGHW hVY JCUjd dYde EYQGH GdbQBf(B. (3abO Ufa GdYdeGA Ydi JYGbH GdCReGf eG dG jMUi ef GdeUfaGJ aj EYQGH GdbQBf hdGMX HYV GdeMbbjf efge Cfge JbjOhG aj EYQGHgG ddbQBf HbhGYO eMOOI hef Ke fU GdYcHQj(B-(3hgh ef CHQR GdeUfajf aj EYQGH GdbQBf(B-(3aj HOGjI Hd CUdG dZjQg ef GdYdhe(B. (3cJGHg Ydi chfg YdeG ZjQ Cf GdYcHQj de jJYO gPg GdedGMXI Edi eMGhdI dJCUjd gPG GdYde hPdc HLeY TJGJ bhGYO jcTa Yf VhGHW YdejI GdJhLjg GdJj MceJ Yed GdYdeGA aj EYQGHge ddbQBf hJUfjagG JUfjaG gPG GdYde hCUhdg hgPG GdGSJbUGA ef GdUYhHI HecGf EP jbJVj eQGLYI hOQGSI dYTQGJ ef GdeUfaGJ aj EYQGH GdbQBf hef Ke jXd eLGd GdHMK eaJhMG hbO ChdjfG YfGjJfG HGdCUhd hGdbhGYO GdYGeI GdJj GJab YdjgG CcKQ GdYdeGA CeG eG CfaQO Hg HYVge hde hQHeG CgedfGg dCfg dG jeKd CUdG hdG VGHW jfGd bHhd SGFQge aQHeG CTQfG Edjg cGJLGg dHYVge CMjGfG(B. (3YGeG hCfj dCQLh Cf jchf gPG GdcJGH aGJMI NjQ dOQGSGJ eJYebI aj Yde EYQGH GdbQBf(B.s
(3HHdjhLQGajI (B: (3UaMI (B317-334.s
Keywords: (3GdbQBf s -- (3EYQGH s